1990
DOI: 10.1111/j.1365-2494.1990.tb01968.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fertilizer nitrogen source and cattle slurry on herbage production and nitrogen utilization

Abstract: A field plot experiment was carried out on an established grassland sward from 1983 -88 inclusive to examine the effects of time of application, chemical form of nitrogen (N) and cattle slurry dry matter (DM) content on yield and efficiency of N use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
1
1
1
Order By: Relevance
“…, 1991). The N‐use efficiency of that applied in the slurry treatments in this study was higher than typically obtained in surface applications to grassland (Long and Gracey, 1990). The relatively mild winters and the growth rates of Italian ryegrass in winter could possibly have promoted the high N‐use efficiency found in treatments where slurry was applied at three different times of the year (treatments T3 and T4) when compared with treatment T2 with total application of slurry in spring, contrasting with results obtained by Sieling et al.…”
Section: Resultscontrasting
confidence: 60%
“…, 1991). The N‐use efficiency of that applied in the slurry treatments in this study was higher than typically obtained in surface applications to grassland (Long and Gracey, 1990). The relatively mild winters and the growth rates of Italian ryegrass in winter could possibly have promoted the high N‐use efficiency found in treatments where slurry was applied at three different times of the year (treatments T3 and T4) when compared with treatment T2 with total application of slurry in spring, contrasting with results obtained by Sieling et al.…”
Section: Resultscontrasting
confidence: 60%
“…Larger amounts of N, but also other nutrients, in T2 caused a significantly higher DM yield in 1999 and 2000 (72 and 111%, respectively) compared to T1 (Table 1), primarily due to the positive action of N on grass yield in the first cuts. The trend reported by Long and Gracey (1990) of a slurry-fertilizer combination being more effective than inorganic fertilizer at the 1 st harvest, followed by little difference in the response to N source at the 2 nd harvest, was confirmed in this research as well (data not shown). According to the authors, the reasons for such trends might be higher ammonia losses in warmer and drier conditions at the time of summer applications of slurry, for the first regrowth, compared to equivalent spring-time applications.…”
Section: Resultssupporting
confidence: 80%
“…These results have the same trend as the studies by Lim et al (2003), Choi and Yook (2000), and Lim et al (2006). On the effect of application of LSM compared to CF, Jin et al (1996) claimed that the animal manure application increased maize production by the chemical improvement of soil, Pain et al (1986) and Long and Gracey (1990) reported that the application of low concentration LSM in high temperature drought period increased the production of forage crops, because it reduced moisture stress owing to the supply of a large amount of water in addition to the fertilizer effect.…”
Section: Methodsmentioning
confidence: 99%